PALIDOTOMI UNTUK PENYAKIT PARKINSON LAPORAN 3 KASUS - Muhammad Agus Aulia,* Adolf Setiabudi,* Handrianto Setiajaya,* Agus Yunianto,* Lukman Maruf* (NEURONA, 2018)
FOR PARKINSONS DISEASE HAS RECENTLY DEVELOPED IN INDONESIA FOR THE LAST 6 YEARS UNLIKE DEEP BRAIN STIMULATION DBS IMPLANTATION PALLIDOTOMY PROCEDURE IS FULLY COVERED BY INDONESIAN NATIONAL HEALTH INSURANCE THEREFORE IT IS EXPECTED THAT THIS PROCEDURE COULD BE PERFORM TO ALL INDICATED PARKINSONS DISEASE PD PATIENTS